2015
DOI: 10.1038/npp.2015.163
|View full text |Cite
|
Sign up to set email alerts
|

Hunger Promotes Fear Extinction by Activation of an Amygdala Microcircuit

Abstract: Emotions control evolutionarily conserved behavior that is central to survival in a natural environment. Imbalance within emotional circuitries, however, may result in malfunction and manifestation of anxiety disorders. Thus, a better understanding of emotional processes and in particular the interaction of the networks involved is of considerable clinical relevance. Although neurobiological substrates of emotionally controlled circuitries are increasingly evident their mutual influences are not. To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 50 publications
6
67
1
Order By: Relevance
“…In addition, given that rats eventually shifted their behaviour when confronted with a high level of shock, the first explanation that CeA activation heightens motivation in such a way that it overpowers aversive consequences appears more likely. This interpretation is further supported by a study showing that hunger‐induced activation of a CeA‐BLA microcircuit promotes extinction of fear responses, suggesting that intense motivation driven by the CeA may override existing fear of aversive consequences (Verma et al., ).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, given that rats eventually shifted their behaviour when confronted with a high level of shock, the first explanation that CeA activation heightens motivation in such a way that it overpowers aversive consequences appears more likely. This interpretation is further supported by a study showing that hunger‐induced activation of a CeA‐BLA microcircuit promotes extinction of fear responses, suggesting that intense motivation driven by the CeA may override existing fear of aversive consequences (Verma et al., ).…”
Section: Discussionmentioning
confidence: 73%
“…Recent evidence suggests that central NPY inhibits the expression and promotes the extinction of learned fear (Gutman et al , ; Fendt et al , ; Verma et al , ). Furthermore, we demonstrated that short‐term fasting impairs fear consolidation but facilitates fear extinction by increasing feedforward inhibition in an amygdala microcircuit (Verma et al , ). This feedforward inhibition was reduced in Y4KO mice resulting in impaired fear extinction.…”
Section: Introductionmentioning
confidence: 86%
“…For example, fasting prior to fear conditioning impairs fear acquisition, but fasting prior to extinction improves extinction learning (Verma et al, 2015). NPY may play a critical role as it modulates both NE and CRH activity, resulting in the attenuation of anxiety-like behavior and HPA axis activity (Hastings et al, 2004; Rasmusson et al, 2000; Sah and Geracioti, 2013).…”
Section: Delineating the Relationships: Insight From Animal Modelsmentioning
confidence: 99%